Anti-inflammatory effect of different curcumin preparations on adjuvant-induced arthritis in rats - Ieva Rinkunaite; Egidijus Simoliunas; Milda Alksne; Dominyka Dapkute; Virginija Bukelskiene (BMC, 2021)
Abstract Background Curcumin, a natural polyphenolic substance, has been known for more than two millennia as having strong anti-inflammatory activity towards multiple ailments, including arthritis. The main drawback of curcumin is its poor solubility in water, which leads to low intestinal absorption and minimal bioavailability. In this study, we aimed to compare the anti-arthritic in vivo effect of different curcumin preparations - basic curcumin extract, micellar curcumin, curcumin mixture with piperine, and microencapsulated curcumin. Methods Arthritis was induced in Wistar rats by complete Freund's adjuvant, and the severity of arthritis was evaluated daily using the arthritis score system. Curcumin preparations were given to animals per os daily for 20 consecutive days, starting at 6th day after arthritis induction. To determine the inflammatory background, pro-inflammatory cytokines were determined using the ELISA test. In addition, hematologic test, weight change, and limb swelling were tracked. Results Our results indicate that curcumin had a rather weak effect on arthritis progression in the Wistar rat model, microencapsulated curcumin effectively prevented the progression of arthritis - the disease stabilized after 10 days of supplementation. It also reduced the levels of immune cells (neutrophils and leukocytes), as well as pro-inflammatory cytokines - TNFα, IL-1, and IL-6, which levels were close to arthritis-free control. Other formulations of curcumin had lower or no effect on arthritis progression. Conclusion Our study shows that the same concentrations of curcumin had a distinctly expressed positive anti-inflammatory effect depending on the form of its delivery. Specifically, we found that microencapsulated curcumin had the most promising effect for treatment. Graphical abstract